Pre-Columbian Jamaica - Allsworth-Jones, P. (Philip) (Caribbean archaeology and ethnohistory., 2008)
Intends to summarize the prehistoric evidence from the island of Jamaica. This book is designed to provide general commentary that can stand alone and be read as a continuous narrative. It includes a CD-ROM that furnishes a range of illustrations, data, calculations, measurements, and comparisons.